Empowering Diverse Faith Communities through Engagement in Participatory Science. - Wolf-Chase, Grace A.; Hinman, Katharine E.; Trouille, Laura (Zygon: Journal of Religion & Science, 2024)
Developing successful strategies that promote meaningful dialogue between scientific and religious communities is arguably one of the most urgent issues of our time. Perceptions of science as hostile to religion have led governments to adopt educational policies that are not in the best interest of communities and adversely affect participation in science by people of faith, disproportionately excluding minorities and women (e.g., Bolger and Ecklund 2022; Barnes and Brownell 2018; Ecklund et al. 2019). Diversifying science requires respectfully and constructively engaging with diverse worldviews and cultures. One way this can be accomplished is through collaborative projects that facilitate building relationships across communities that might not otherwise interact.